Behavioural and neurochemical effects of phosphatidylserine in MPTP lesion of the substantia nigra of rats - Perry, J. C.; Da Cunha, C.; Anselmo-Franci, J.; Andreatini, R.; Miyoshi, E.; Tufik, S.; Vital, MABF (Elsevier B.V., 2004)
The present study investigated the effects of intranigral MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) infusion on rats treated with phosphatidylserine and evaluated in two memory tasks and on striatal dopamine levels. The results indicated that MPTP produced a significant decrease in the avoidance number in comparison to sham-operated and non-operated rats submitted to a two-way avoidance task. MPTP-lesioned rats exhibited an increase in the latencies to find the platform in cued version of the water maze in comparison to sham-operated and non-operated animals. The tested toxin reduced striatal dopamine levels in comparison to sham-operated and non-operated groups. A final surprising result was that phosphatidylserine was unable to reverse the cognitive deficits produced by MPTP or the reduction of striatal dopamine levels. In conclusion, the data suggest that MPTP is a good model to study the early impairment associated with Parkinson's disease and phosphatidylserine did not improve the memory impairment induced by MPTP. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: phosphatidylserine; MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine); memory; (Rat); Parkinson's disease; dopamine